“Measurement and Evaluation” Course in Face-to-Face and Distance Education - Aliustaoğlu, Feyza (IGI Global, 2022)
This chapter covers the examples of applications for the implementation of the “Measurement and Evaluation” course in face-to-face and distance education processes in mathematics education and the prospective mathematics teachers' opinions about these applications. The course took 14 weeks to complete: 6 weeks of face-to-face education and 8 weeks of distance education due to the COVID-19 outbreak. At the end of the semester, the opinions of the prospective mathematics teachers were taken about face-to-face and distance education. Prospective teachers generally stated that they found the course videos useful for understanding the subject, the assignments helped them consolidate the learned subject, and the third assignment in particular was comprehensive and useful. They stated that face-to-face education was advantageous in terms of being able to ask questions and active participation, and distance education was advantageous in terms of being able to watch the course videos again.
Keywords: 4. Education